Addressing climate change: the application of Islamic principles and values by a non-governmental organization (NGO) - Rabi'ah Binte Ghazali (International Institute of Islamic Thought and Civilization, IIUM, 2012)
This thesis addresses practical Islamic applications to climate change by looking at a case study of an Islamic environmental NGO in Indonesia, LPBI-NU. A variety of qualitative research methods were used as part of the overarching approach adopted by the thesis. The case study of LPBI-NU was set in the context of issues such as the role of religion in addressing environmental degradation and the compatibility between religion and civil society. Though religion and civil society has long been deemed to be incompatible, this thesis argues that the urgency of today's environmental crises has made it a matter of critical importance to infuse civil society with a religious discourse. To take the argument beyond theory, an inquiry into LPBI-NU's operations sought to uncover useful lessons on how an Islamic organisation can participate in civil society to address climate change. The organisation, with its vision of bringing about raÍmatan lil 'ālamīn (blessings to all mankind) via the application of tawassuÏ (moderation), tawāzun (balance) and tasāmuḥ (tolerance), showcases a promising strategy of engaging the Muslim masses by using the familiar vocabulary of the Qur'ān on the one hand, and collaboration with the state to address practical policy issues on the other.